Iconographic Similarities Between Permian “Goddess Plaques” (Ural Region, 7-8th Centuries CE) and Horus Cippi (Egypt, 8th Century BCE - 2nd Century CE) - Graham, Lloyd D. (Eikón / Imago, 2020)
The iconography of the Horus cippus, an amulet popular in Egypt from the late Third Intermediate Period to Roman times (8thcentury BCE - 2nd century CE), is unexpectedly recapitulated in bronze “goddess plaques” of the 7-8th centuries CE made by Permian peoples – Finno-Ugric groups from the Ural region of northern Eurasia. The likely explanation is that both templates are descendants of the widely-diffused “Master of Animals” motif, which originated in Mesopotamia during the Ubaid period (6-5thmillennium BCE). Transfer of the Master/Mistress of Animals motif from the Near East to the Ural region probably occurred via the Scythians of the 1st millennium BCE.